Forecasting the long-term activity of deep-seated landslides via groundwater flow and slope stability modelling - Preisig, Giona (My University, 2020)
Large (deep-seated) landslides present complex geometries, rock/soil properties, and kinematical behavior. Complex geometries are due to the presence of several sliding zones, while complex properties typically result from the dilation, compression, or fatigue of geologic materials. Kinematical behavior is often episodic, with periods of stability followed by periods of enhanced slope movements owing to shear strength reduction in response to groundwater pressure changes. These mechanisms complicate our capacity in forecasting the long-term activity and thus, the choice of a strategy for hazard management. This technical note introduces a method for predicting the long-term activity of deepseated landslides based on one-way coupled hydromechanical numerical modelling. The method is applied to analyse the longterm stability of a deep-seated compound slide in the Swiss Jura Mountains. Results indicate that, under natural groundwater pressure changes, the analysed compound slide will continue to move in an episodic fashion in response to groundwater levels in the slope, without developing velocities greater than several centimeters per year. This example demonstrates how one-way coupled hydromechanical modelling constrained by field data is a reliable tool for assessing the long-term activity of deep-seated landslides and helping the management of associated hazards.
Keywords: Long-term forecasting . Hydromechanical modelling . Slope hydrogeology . Deep-seated compound slides . Swiss Jura Mountains